Trauma patients with the 'triad of death'. Issue 8 (23rd July 2011) - Mitra, Biswadev; Tullio, Francesca; Cameron, Peter A; Fitzgerald, Mark
Abstract : Introduction: Injured patients presenting with hypothermia, acidosis and coagulopathy have been identified at high risk of death. This study aimed to describe the presentation, management and outcome of major trauma patients presenting with the 'triad of death' and identify ways to improve survival. Methods: A retrospective, explicit chart review was undertaken on patients presenting to a level I adult major trauma centre with the 'triad of death'. These patients presented directly from the scene, were coagulopathic (international normalised ratio (INR) >1.5), hypothermic (temperature <35°C) and acidotic (pH <7.2) on arrival. Results: There were 90 patients over an 8-year period, with an overall mortality of 47.8%. No significant differences were observed among demographics and injury severity scores between survivors and non-survivors. Extremes of systolic blood pressure and heart rate, a high activated partial thromboplastin time activated partial thromboplastin time, low fibrinogen counts, pH, bicarbonate, base excess and haemoglobin were present among survivors. There were no survivors in our cohort with an initial INR greater than 3.2. Survivors received significantly lower volumes of packed red blood cells. Conclusions: There has been little change in mortality over time in this subgroup of major trauma patients. While the presence of the triad alone does not determine futility, there were no survivors over 8 years with extreme coagulopathy with concurrent hypothermia and acidosis.